Leflunomide induced drug reaction with eosinophilia and systemic symptoms: A lesser known entity - Deepak Vashisht; Madhab Durga Tripathy; Sunmeet Sandhu; Rohit Kothari; Surbhi Vashisht; Arun Hegde (Indian Journal of Rheumatology)
Drug reaction with eosinophilia and systemic symptoms (DRESS) is a severe cutaneous adverse reaction to drugs with varied clinical manifestations. Diffuse morbilliform rash with facial edema and systemic involvement in the form of lymphadenopathy, eosinophilia and hepatic involvement are the commonest clinical presentation. Features mimicking Stevens-Johnson syndrome and toxic epidermal necrolysis (SJS-TEN), sepsis, Kawasaki disease andhyper-eosinophilic syndrome can cause immense diagnostic dilemma. We report a case of DRESS which is unique as the triggering drug being leflunomide that has rarely been reported and atypical presentation wherein exfoliative dermatitis and erythema multiforme like lesions which evolved sequentially. A 56-year-old lady, a known case of rheumatoid arthritis on treatment, developed diffuse exanthematous rash over body with fever and hepatic dysfunction, a month after administration of leflunomide. She was diagnosed as DRESS partially managed with steroids to rebound back a week later with severe and atypical manifestations. The uniqueness of the case lies in the fact that DRESS resulted after an uncommon incriminating drug and polymorphic presentation appearing sequentially, besides, highlighting the need of slow tapering of steroids.